POLITIK HUKUM KEPEMILIKAN ASING PADA PERBANKAN NASIONAL (LAW POLITIC OF THE FOREIGN OWNERSHIP IN THE NATIONAL BANKS) - Dian Cahyaningrum (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2015)
The increasing of foreign ownership of shares in the national banks is currently quite disturbing. This is due the laws and regulations of banking sector that open opportunities for foreigners to own shares of the bank up to 99%. This opportunity is meant to broden share ownership of banks and facilitate the bank to improve its capital structure. In fact, these laws have created positive and negative implications. This positive implications are namely the creation of Good Corporate Governance and the increasing performance of the bank. However, these laws can also cause negative implications, which are bank will be controlled by foreigners; will be contracted market share of bank owned by Indonesian citizens and/or legal entities; banks tend to provide consumer credit; revenue and profit recorded in foreign bank; the high risk of capital flight out of the country in case of a crisis. Concerning the positive and negative implications, it is important to conduct in depth assessment of whether or not the foreign ownership of shares in the national bank should be restricted in the law.ABSTRAKMeningkatnya kepemilikan asing atas saham bank yang saat ini meresahkan disebabkan peraturan perundang-undangan sektor perbankan membuka kesempatan bagi asing untuk memiliki saham bank hingga mencapai 99%. Dibukanya kesempatan ini dimaksudkan untuk memperluas kepemilikan saham bank dan mempermudah bank untuk meningkatkan struktur permodalan.Pengaturan ini menimbulkan implikasi positif, yaitu terciptanya Good Corporate Governance dan meningkatnya kinerja bank. Namun pengaturan tersebut juga dikhawatirkan dapat menimbulkan implikasi negatif yaitu bank dikendalikan oleh asing; terdesaknya pangsa pasar bank yang dimiliki Warna Negara Indonesia dan/atau Badan Hukum Indonesia; bank cenderung memberikan kredit konsumtif; penghasilan dan keuntungan bank disimpan di luar negeri; dan tingginya risiko pelarian modal ke luar negeri jika terjadi krisis. Sehubungan dengan implikasi positif dan negatif tersebut, perlu ada pengkajian yang mendalam mengenai perlu atau tidaknya pembatasan kepemilikan asing atas saham bank dalam Undang-Undang.